MENGANGKAT KEKAYAAN SUMBER DAYA ALAM MELALUI KERAJINAN TANGAN TRADISIONAL DI DESA KENARIMBALA KECAMATAN ALOR TIMUR LAUT KABUPATEN ALOR - Matheos E. Maure; Marni S. Laure; Mehelina R. Lebo; Petrus Mau Tellu Dony (JOURNAL OF COMMUNITY DEDICATION, 2026)
This research aims to Highlight the Richness of Natural Resources Through Traditional Handicrafts in Kenarimbala Village, North East Alor District, and the character values contained in the handicrafts. The researcher used a qualitative method. Data analysis techniques were carried out by data reduction, data presentation, and drawing conclusions. This research was conducted in Alata village, Kenarimbala Village, North East Alor District. The informants in this study were the Kenarimbala Village officials and the Elderly. The results of the study show that: Highlighting the Richness of Natural Resources Through Traditional Handicrafts in Alata village brings several benefits to the local community, namely: (1) providing positive value in managing local wisdom for the progress of the village, and (2) revitalizing traditional handicrafts so that they do not become extinct with the times. The research results can be concluded that the implementation process of Highlighting the Richness of Natural Resources Through Traditional Handicrafts in Alata village, Kenarimbala Village, involves traditional handicrafts managed by the elderly in the village.